Optimizing solar dish concentrator efficiency with nanofluids and diverse cavity design - Muhammad Ilham, Maulana; Mohd Fairusham, Ghazali; Arman, Abdullah; Nor Azwadi, Che Sidik; Najafi, Gholamhassan; Rostami, Mohammadreza Hasandust; Najafpour, Ahmad (Semarak Ilmu Publishing, 2024)
The quest for enhanced efficiency in solar energy systems has directed significant attention towards optimizing solar dish concentrators. This study investigates the performance enhancement of solar dish concentrators through the use of advanced nanofluid solutions and innovative cavity designs. The experimental setup includes various nanofluid concentrations and different cavity geometries to evaluate their impact on the overall efficiency of the system. Experimental and numerical results demonstrate a marked improvement in thermal performance, with nanofluid and cavity designs achieving up to 12% increase in efficiency compared to conventional systems. The results revealed that the hemispherical and the cubical cavities are the most effective designs, while the cylindrical cavity presents lower performance. The findings provide valuable insights into the potential of nanofluid-based solar dish concentrators and underline the importance of cavity design in optimizing solar energy harnessing. This study lays the groundwork for future research and development in high-efficiency solar energy systems, contributing to the advancement of suitable and renewable energy technologies.